Usability Analysis of the IBOSS PTSP BP Batam User Interface Using Heuristic Evaluation - Alamandha, Bintang Febrian; Yulius, Rina (Asosiasi Doktor Sistem Informasi Indonesia, 2024)
This research investigates user dissatisfaction with the IBOSS user interface, reported by 54% of users in an initial survey, and aims to improve the interface through heuristic evaluation and subsequent redesign using Gestalt principles. The usability of the IBOSS user interface was assessed using the heuristic evaluation method, focusing on 10 usability variables. Among the 10 heuristic variables, only the ‘Aesthetics and Minimalist Design’ variable was rated positively, with a score of 78% and was considered satisfactory with no need for improvement. Based on the evaluation results, the interface was redesigned using Gestalt principles to improve user experience. After the redesign, interviews with experts showed a significant improvement in the user interface. The experts gave positive feedback compared to their assessment before the redesign. The heuristic evaluation identified key areas for improvement in the IBOSS user interface, excluding aesthetic aspects. Applying Gestalt principles in the redesign process resulted in improved usability and received favourable feedback from experts, indicating the success of the redesign effort.